(untitled) (International journal of artificial intelligence, 2024)
This article explores the vital role of intellectually gifted and talented youth in shaping the foundation of a nation. It highlights the importance of fostering intellectual capacity, nurturing creativity, and encouraging innovation for sustainable national progress. The article emphasizes the need for robust educational systems, global collaboration, and moral responsibility among young people. By investing in the development of intellectual talent, nations can secure their future prosperity and global standing.